PERAN GAYA KEPEMIMPINAN TRANSFORMASIONAL MEMODERASI PENGARUH MOTIVASI KERJA DAN KOMPETENSI TERHADAP KINERJA GURU SMP DI KECAMATAN JAKENAN KABUPATEN PATI - Sutarto, 11.5202.0013 (Students Journal of Economic and Management, 2013)
The purpose of this study to determine the effect of work motivation and competency on teacherâs performance moderated by the transformational leadership style. This research was conducted with a sensus method and implemented in the sub-district Jakenan Pati. Technical test data used in this study include validitas test, reliability test, classical assumption test, multiple regression analysis, t test, and mediation test to verify and prove the hypothesis of the research. Tested the validity of data collected by viewing at the magnitude of the KMO values above 0.5 could be declared valid. The results demonstrate the validity of the KMO test for work motivation is 0.619, KMO test for competency is 0.837. KMO test for transformational leadership style is 0.816 and KMO test for the performance is 0.894. It can be said that all variables declared valid. Its reliability test showed the 0.663 for work motivation, 0.927 for competency, 0,891 for transformational leadership style and 0.881 for performance. These show that all variables are reliable. From the analysis and discussion show that a significant positive influence work motivation on performance, significantly positive effect of competency on performance. transformational leadership style has not moderating the influence of work motivation on the performance of teachers. transformational leadership style has not moderating the influence of competency on the performance of teachers. Â Keywords: Work Motivation, Competency, Transformational Leadership Style and Performance